Dies the fire - Stirling, S. M. (Stirling, S. M. Emberverse., 2005)
When a strange electrical storm over the island of Nantucket suddenly causes all electronic devices to cease functioning, the world is faced with an unimaginable transformation, one that is complicated by some individuals' ruthless quest for ultimate domination.